2013
DOI: 10.1001/jama.2012.188351
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric Readmission Prevalence and Variability Across Hospitals

Abstract: Context Readmission rates are used as an indicator of the quality of care that patients receive during a hospital admission and after discharge. Objective To determine the prevalence of pediatric readmissions and the magnitude of variation in pediatric readmission rates across hospitals. Design, Setting, Patients We analyzed 568,845 admissions at 72 children's hospitals between 7/1/2009 and 6/30/2010 in the National Association of Children's Hospitals and Related Institutions Case Mix dataset. We estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
302
8
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 377 publications
(341 citation statements)
references
References 39 publications
17
302
8
14
Order By: Relevance
“…27,[32][33][34][35] Recent multicenter data have shown that asthma was in the top 10 admission diagnoses in pediatric patients, with the highest readmission rate of 10.6% within the first year after discharge. 5,36 These studies suggest that targeting care coordination for ambulatory care-sensitive conditions, such as asthma, may also have an impact on health care expenditures. At KMCWC, the Pediatric Hospitalist Division cares for ∼85% of all inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…27,[32][33][34][35] Recent multicenter data have shown that asthma was in the top 10 admission diagnoses in pediatric patients, with the highest readmission rate of 10.6% within the first year after discharge. 5,36 These studies suggest that targeting care coordination for ambulatory care-sensitive conditions, such as asthma, may also have an impact on health care expenditures. At KMCWC, the Pediatric Hospitalist Division cares for ∼85% of all inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 More specifi cally, the 30-day readmission rate for children who are typically developing and without chronic illness is 3.1%. 3 For children with a single complex chronic condition and/or technology assistance, the rate of readmission to an acute care hospital has been reported to be up to 25% within 30 days of a previous hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition is emerging of the need to develop a DP model to address the transitional care needs of families of children with medical complexities (Berry, Agrawal, Cohen, & Kuo, 2013). These families may have difficulties with access to care and limited resources that place them at risk for adverse outcomes such as readmissions (Berry, Toomey, et al, 2013 andSrivastava andKeren, 2013). To advance the development and testing of DP interventions for pediatric patients, a clear delineation of the actions and activities within a pediatric DP model of care is needed.…”
Section: Applied Nursingmentioning
confidence: 99%